Facet-Control versus Co-Catalyst-Control in Photocatalytic H2 Evolution from Anatase TiO2 Nanocrystals - Qin, Shanshan; Shui, Lancang; Osuagwu, Benedict; Denisov, Nikita; Tesler, Alexander B; Schmuki, Patrik (ChemistryOpen, 2022)
Titanium dioxide (TiO2 ) and, in particular, its anatase polymorph, is widely studied for photocatalytic H2 production. In the present work, we examine the importance of reactive facets of anatase crystallites on the photocatalytic H2 evolution from aqueous methanol solutions. For this, we synthesized anatase TiO2 nanocrystals with a large amount of either {001} facets, that is, nanosheets, or {101} facets, that is, octahedral nanocubes, and examined their photocatalytic H2 evolution and then repeated this procedure with samples where Pt co-catalyst is present on all facets. Octahedral nanocubes with abundant {101} facets produce >4 times more H2 than nanosheets enriched in {001} facets if the reaction is carried out under co-catalyst-free conditions. For samples that carry Pt co-catalyst on both {001} and {101} facets, faceting loses entirely its significance. This demonstrates that the beneficial role of faceting, namely the introduction of {101} facets that act as electron transfer mediator is relevant only for co-catalyst-free TiO2 surfaces.
Keywords: anatase TiO2; Pt co-catalyst; photocatalytic H2 evolution; crystal facet engineering